2021
DOI: 10.1103/physrevlett.127.237002
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Nature of Spontaneous Magnetic Fields in Superconductors with Time-Reversal Symmetry Breaking

Abstract: We present a systematic investigation of muon-stopping states in superconductors that reportedly exhibit spontaneous magnetic fields below their transition temperatures due to time-reversal symmetry breaking. These materials include elemental rhenium, several intermetallic systems and Sr2RuO4. We demonstrate that the presence of the muon leads to only a limited and relatively localized perturbation to the local crystal structure, while any small changes to the electronic structure occur several electron volts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Therefore, there is no TRS breaking, excluding the existence of triplet pairing [23]. Recently, it is reported that muon could modify its local environment in ZF µSR, making µSR results on TRS differ from other techniques [36]. This is not in our case since our result is consistent with previous µSR work, and there is no results using other techniques to study TRS so far.…”
Section: A Zf-µsrsupporting
confidence: 79%
“…Therefore, there is no TRS breaking, excluding the existence of triplet pairing [23]. Recently, it is reported that muon could modify its local environment in ZF µSR, making µSR results on TRS differ from other techniques [36]. This is not in our case since our result is consistent with previous µSR work, and there is no results using other techniques to study TRS so far.…”
Section: A Zf-µsrsupporting
confidence: 79%
“…Both free-and fixed- ZF analyses show a robust increase in  ZF (T) below T c , further confirming that the signal of spontaneous magnetic fields is an intrinsic effect. Very recently, theoretical works have confirmed the intrinsic nature of spontaneous magnetic fields in superconductors with TRS breaking (52). The ground-state spontaneous fields can be estimated by using B spont.…”
Section: Zf-sr and Trs Breakingmentioning
confidence: 95%
“…Therefore, there is no TRS breaking, excluding the existence of triplet pairing [23]. Recently, it is reported that although the positive charge of muon could modify the local environment in ZF-μSR experiments, TRS property shown by μSR is intrinsic since the effect induced by muon's charge is several eV below Fermi energy, which is much larger than the magnitude of superconducting gap (at the decade of meV) [36].…”
Section: Zf-μsrmentioning
confidence: 98%